Characterization of Endophytic Streptomyces griseorubens MPT42 and Assessment of Antimicrobial Synergistic Interactions of Its Extract and Essential Oil from Host Plant Litsea cubeba - Quang Huy Nguyen; Hai Van Nguyen; Thi Hanh-Nguyen Vu; Son Chu-Ky; Thu Trang Vu; Ha Hoang; Ngoc Tung Quach; Thi Lien Bui; Hoang Ha Chu; Thi Nhan Khieu; Samira Sarter; Wen-Jun Li; et al. (MDPI AG, 2019)
The present study aimed to evaluate the synergistic effects of the crude ethyl acetate extract (CEAE) from endophytic actinomycete MPT42 and essential oil (EO) of the same host plant Litsea cubeba. The isolate MPT42, exhibiting broad-spectrum antimicrobial activities and harboring all three antibiotic-related biosynthetic genes pks-I, pks-II, and nrps, was identified as Streptomycete griseorubens based on an analysis of the morphology, physiology, and 16S rDNA sequence. Minimum inhibitory concentrations (MICs) and the fractional inhibitory concentration index were used to estimate the synergistic effects of various combined ratios between CEAE or antibiotics (erythromycin, vancomycin) and EO toward 13 microbial strains including pathogens. L. cubeba fruit EO, showing the main chemical constituents of 36.0% citral, 29.6% carveol, and 20.5% limonene, revealed an active-low against tested microbes (MICs ≥ 600 μg/mL). The CEAE of S. griseorubens culture exhibited moderate−strong antimicrobial activities against microbes (MICs = 80−600 μg/mL). Analysis of the mechanism of action of EO on Escherichia coli ATCC 25922 found that bacterial cells were dead after 7 h of the EO treatment at 1 MIC (5.5 mg/mL), where 62% cells were permeabilized after 2 h and 3% of them were filament (length ≥ 6 μm). Combinations of CEAE, erythromycin, or vancomycin with EO led to significant synergistic antimicrobial effects against microbes with 4−16 fold reduction in MIC values when compared to their single use. Interestingly, the vancomycin−EO combinations exhibited a strong synergistic effect against five Gram-negative bacterial species. This could assume that the synergy was possibly due to increasing the cell membrane permeability by the EO acting on the bacterial cells, which allows the uptake and diffusion of antimicrobial substances inside the cell easily. These findings in the present study therefore propose a possible alternative to combat the emergence of multidrug-resistant microbes in veterinary and clinics.